KDM5-mediated transcriptional activation of ribosomal protein genes alters translation efficiency to regulate mitochondrial metabolism in neurons - Yheskel, Matanel; Hatch, Hayden A M; Pedrosa, Erika; Terry, Bethany K; Siebels, Aubrey A; Zheng, Xiang Yu; Blok, Laura E R; Fencková, Michaela; Sidoli, Simone; Schenck, Annette; Zheng, Deyou; Lachman, Herbert M; et al. (Nucleic acids research, 2024)
Genes encoding the KDM5 family of transcriptional regulators are disrupted in individuals with intellectual disability (ID). To understand the link between KDM5 and ID, we characterized five Drosophila strains harboring missense alleles analogous to those observed in patients. These alleles disrupted neuroanatomical development, cognition and other behaviors, and displayed a transcriptional signature characterized by the downregulation of many ribosomal protein genes. A similar transcriptional profile was observed in KDM5C knockout iPSC-induced human glutamatergic neurons, suggesting an evolutionarily conserved role for KDM5 proteins in regulating this class of gene. In Drosophila, reducing KDM5 changed neuronal ribosome composition, lowered the translation efficiency of mRNAs required for mitochondrial function, and altered mitochondrial metabolism. These data highlight the cellular consequences of altered KDM5-regulated transcriptional programs that could contribute to cognitive and behavioral phenotypes. Moreover, they suggest that KDM5 may be part of a broader network of proteins that influence cognition by regulating protein synthesis.
Keywords: aktivace transkripce; Drosophila melanogaster; Drosophila Proteins; Mitochondria; Intellectual Disability; proteiny Drosophily; Ribosomal Proteins; Protein Biosynthesis; proteosyntéza; Transcriptional Activation; neurony; ribozomy; Drosophila; ribozomální proteiny; Ribosomes; Animals; lidé; histondemethylasy; Humans; zvířata; Neurons; Histone Demethylases; mitochondrie; mentální retardace